Dampak Lingkungan Keuangan terhadap Nilai Perusahaan pada Industri Pertambangan - Saputra, Briyan Dwi; Rasjid, Herlina; Amali, Lanto Miriatin (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research aims to analyze and determine the influence of the financial environment on company value in the oil and gas sub-sector mining industry listed on the BEI in 2017-2022. The population here is all oil and gas subsector companies listed on the Indonesia Stock Exchange (BEI) in 2017-2022. The sampling technique in this research used a purposive sampling method with a sample size of 30 people. The data collection technique in this research uses documentation techniques, namely looking for financial report data published by companies from 2017 to 2022. The analytical test used to test this research is multiple linear regression analysis. The research results show that the liquidity ratio has no partial effect on company value. The activity ratio has a partial effect on company value, the leverage ratio has a partial effect on company value, and the profitability ratio has a partial effect on company value. Then the financial environment simultaneously influences company value. The financial environment influences company value with a coefficient of determination of 42.7% while the remaining 57.3% is influenced by other variables not examined in this research.